Implementasi program kampus mengajar 6: sebagai peningkatan literasi dan numerasi di SDN 256/VI Pematang Kancil II - Wijayanti, Chandra; Muhammad Sofwan (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2024)
The aim of this research is to enhance students' literacy and numeracy skills through the Campus Teaching Program. The program involves students as volunteers teaching in schools in remote areas facing challenges in literacy and numeracy. The method applied in this program is through an interactive and participatory approach. Students collaborate with teachers in schools to design and implement creative and engaging learning strategies. They utilize various materials and resources to boost students' interest and understanding in literacy and numeracy. This community service activity is conducted at SDN 256/VI Pematang Kancil II in the Pemenang Subdistrict, Merangin Regency, and spans for 4 months from August 14, 2023, to December 5, 2023. The final outcomes of the Campus Teaching Program significantly improved the literacy and numeracy skills of students at SDN 256/VI Pematang Kancil II. After four months of implementation, there was a notable increase in the average literacy score by 79%, compared to the previous 49%, and the numeracy score increased by 88%, compared to the previous 30%, based on pre-test and post-test results. Additionally, student participation in literacy and numeracy activities also significantly increased, demonstrating high interest and motivation. This program provides an opportunity for students to make a positive contribution to primary education, while students benefit from innovative, interactive learning approaches focused on enhancing literacy and numeracy.